Applying Normalisation Process Theory to a peer-delivered complex health intervention for people experiencing homelessness and problem substance use - Rebecca Foster; Hannah Carver; Catriona Matheson; Bernie Pauly; Jason Wallace; Graeme MacLennan; John Budd; Tessa Parkes (Communications Medicine)
Abstract Background The Supporting Harm Reduction through Peer Support (SHARPS) study involved designing and implementing a peer-delivered, harm reduction intervention for people experiencing homelessness and problem substance use. Normalisation Process Theory (NPT) provided a framework for the study. Methods Four Peer Navigators (individuals with personal experience of problem substance use and/or homelessness) were recruited and hosted in six third sector (not-for-profit) homelessness services in Scotland and England (United Kingdom). Each worked with participants to provide practical and emotional support, with the aim of reducing harms, and improving well-being, social functioning and quality of life. NPT guided the development of the intervention and, the process evaluation, which assessed the acceptability and feasibility of the intervention for this cohort who experience distinct, and often unmet, health challenges. While mixed-methods data collection was undertaken, this paper draws only on the qualitative data. Results The study found that, overall, the intervention is feasible, and acceptable to, the intervention participants, the Peer Navigators and staff in host settings. Some challenges were encountered but these were outweighed by benefits. NPT is particularly useful in encouraging our team to focus on the relationship between different aspects of the intervention and context(s) and identify ways of maximising ‘fit’. Conclusions To our knowledge, this is the first application of NPT to this cohort, and specifically by non-clinicians (peers) in non-healthcare settings (homelessness services). Our application of NPT helped us to identify ways in which the intervention could be enhanced, with the key aim of improving the health/well-being of this underserved group.